2020
DOI: 10.1021/acsbiomaterials.9b01493
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired, Artificial, Small-Diameter Vascular Grafts with Selective and Rapid Endothelialization Based on an Amniotic Membrane-Derived Hydrogel

Abstract: Clinical application of the amniotic membrane (AM) in vascular reconstruction was limited by poor processability, rapid biodegradation, and insufficient hemocompatibility. In this work, decellularized AM was digested to a thermosensitive hydrogel and densely cross-linked in the nanoscale as “enhanced” collagenous fibers. Via N-(3-dimehylaminopropyl)-N′-ethylcarbodiimide and N-hydroxysuccinimide (EDC/NHS) catalysis, REDV was further grafted to simulate anticoagulant substances on naturally derived blood vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…The C-terminal and N-terminal closure of REDV peptide does not affect the role of REDV, so REDV has a variety of derivatives. 121 Thiol-ene click reaction 122 EDC/ NHS cross-linking 123 2. In order to achieve better endothelialization in vivo, the combination of REDV peptides with other biological factors is also essential.…”
Section: Peptidementioning
confidence: 99%
“…The C-terminal and N-terminal closure of REDV peptide does not affect the role of REDV, so REDV has a variety of derivatives. 121 Thiol-ene click reaction 122 EDC/ NHS cross-linking 123 2. In order to achieve better endothelialization in vivo, the combination of REDV peptides with other biological factors is also essential.…”
Section: Peptidementioning
confidence: 99%
“…Moreover, while it inhibited platelet activation and hemolysis, this graft enhanced the adhesion and expansion of endothelial cells as well as vascular remodeling and repair. In a similar experiment, Peng et al (2020) used D-double-cross-linked decellularized AM hydrogel grafted with REDV(ArgGlu-Asp-Val) polypeptides which showed excellent mechanical strength and resistance to enzymatic degradation and inhibited hemolysis and coagulation (similar characteristics to the vascular graft developed by Lei et al). Also, the addition of REDV to this structure stimulated natural anticoagulant substances on naturally derived blood vessels.…”
Section: Hydrogel Based On Amniotic Membranementioning
confidence: 99%
“…DOPA‐pCB was the most effective, with fibrin and gross thrombus formation decreasing by 59% and applicable to multiple surface materials. Other biomolecules such as polyelectrolytes, [ 48 ] ACH 11 antithrombotic peptide, [ 49 ] reactive oxygen species (ROS)‐responsive antithrombogenic drug, [ 41 ] and Arg‐Glu‐Asp‐Val (REDV) peptide, [ 50 ] were also embedded or grafted to vascular grafts for anticoagulation. Dextran sulfate was self‐assembled onto an electrospun chitosan/PCL scaffold.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…grafted the REDV peptide, which inhibits nonspecific adhesion of platelets, to decellularized amniotic membrane (AM) hydrogel through EDC/NHS coupling. [ 50 ] Moreover, it has been reported that physical properties such as fiber diameter also affect anticoagulation properties. For example, Yu et al.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%